Los derechos humanos frente a los desafíos de las tecnologías de la información - López Ruiz, Marco Antonio (Universidad Michoacana de San Nicolás de Hidalgo, 2010)
The present thesis is been of an investigation on the effects of the massive irruption of the technologies of the information, in the daily life; mainly, the form in that it has transformed our way to understand the information and the different roads that have been created to consent to her. I look for to analyze their repercussions particularly in the environment of the rights human and the confrontation of these with another type of juridical regulations: we speak then of the possible conflict among the right to the information and the one right to the intimacy and the possible conflict that would have with the regulations relating to the intellectual property in the cyberspace. Before this panorama we could bring up some brief reflections of Ortega and Gasset on the technique because she is developed to an unusual, coarse speed to see the list of inventions that have arisen throughout the XX century to realize its I develop, however, let us clarify that the history of the technique and their influence on the humanity he/she goes back to the man's beginnings; for example, the domestication of animals and plants, creation of utensils, elaboration of crafts, media invention and a long one etc.. This inventions fall in the land of the technique and we can establish a narrow relationship between the technique and the man, or if one wants, between the technique and the Culture.

The present thesis is been of an investigation on the effects of the massive irruption of the technologies of the information, in the daily life; mainly, the form in that it has transformed our way to understand the information and the different roads that have been created to consent to her. I look for to analyze their repercussions particularly in the environment of the rights human and the confrontation of these with another type of juridical regulations: we speak then of the possible conflict among the right to the information and the one right to the intimacy and the possible conflict that would have with the regulations relating to the intellectual property in the cyberspace. Before this panorama we could bring up some brief reflections of Ortega and Gasset on the technique because she is developed to an unusual, coarse speed to see the list of inventions that have arisen throughout the XX century to realize its I develop, however, let us clarify that the history of the technique and their influence on the humanity he/she goes back to the man's beginnings; for example, the domestication of animals and plants, creation of utensils, elaboration of crafts, media invention and a long one etc.. This inventions fall in the land of the technique and we can establish a narrow relationship between the technique and the man, or if one wants, between the technique and the Culture.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2010-0035; Electrónica; Transitor; Computación; Evolución; Futuro; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/65